(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
A retrospective analysis of the medical histories of 183 patients with peritonitis that developed against the background of acute appendicitis in the Bukhara and Vobkent subbranches of the Republican Scientific Center for Emergency Medical Care in 2020-2021 was conducted. Depending on the time of admission to the hospital, all patients were conditionally divided into the following subgroups: 1A - subgroup (n=130) admitted to the hospital within 6-8 hours from the onset of the disease and admitted to the hospital within 16-20 hours from the onset of the disease and underwent appendectomy and drainage of the abdominal cavity 1B - subgroup (n=50), 1B - subgroup (n=3) admitted to the hospital within 21-36 hours from the onset of the disease and underwent appendectomy, sanitation of the abdominal cavity and drainage. The results of the analysis showed that early diagnosis and early appendectomy in patients affected the reduction of the recovery day after the disease and the return to active life.